Impact of religion and spirituality on the incidence of depression and mental health among young adults in the Czech Republic - Brečka, Tibor A.; Ptáček, Radek; Sebalo, Ivan; Anders, Martin; Sebalo Vňuková, Martina (Frontiers in Psychology, 2024)
The issue of the impact of religion and spirituality on mental health is a phenomenon which has recently become increasingly more accentuated. Despite the attention given to the topic, many questions still remain as to whether and how religion and spirituality affect a person's mental wellbeing. In the text below, we have focused on examining the relationship between religion and spirituality and mental health among young adults in the Czech Republic. Research also explored the idea that forgiveness can be viewed as a component of religion or spirituality.The research project was executed in close cooperation with STEM/MARK, a renowned data collection agency. The methodological framework was constructed with a dual focus: leveraging standardized questionnaires to ensure data reliability and comparability while also incorporating tailored questions that delve into the participants' socioeconomic status (SES) and background details. The study unfolded across four online sessions, a format chosen for its convenience and effectiveness in facilitating participant engagement while accommodating our respondents' diverse schedules. The total sample approached comprised of 270 young adults that expressed certain form of religiosity.Results: Forgiveness and the depth of one's personal religious or spiritual history emerged as the most influential factors. Forgiveness was significantly associated with an increase in selfblame (positively), and decrease in refocusing, planning (both negatively), and putting things into perspective (negatively) (Beta = 0.25, Beta = -0.06, and Beta = -0.16, respectively). In contrast, a deeper personal religious history was positively associated with self-blame, rumination, and refocusing (Beta = 0.22, Beta = 0.13, and Beta = 0.15, respectively).The finding that forgiveness may be a risk factor associated with regularly elevated depressive symptoms, stress, and maladaptive coping strategies such as self-blame and ruminating over problems, while negatively affecting physical, psychological, and environmental quality of life, clearly points to the need to examine the inner aspects of individual religions and spiritualities. These findings suggest that religious and spiritual beliefs may play a key role in how people experience and manage the emotional burdens and difficulties of life.